พฤติกรรมการทำงานและสภาพแวดล้อมการทำงานที่ส่งผลต่อความปลอดภัย ในการทำงานของพนักงานสัญชาติเมียนมา กรณีศึกษาโรงงานตัวอย่าง ผลิตน้ำแข็งและน้ำดื่ม จังหวัดสมุทรสาคร - ตรีวิจิตร วรเทพ; ทองชา ปิยวัฒน์; ขนุนทอง วสินธุ์; วชิรสุรงค์ ญานพินิจ; จินงี่ วราภรณ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine work behavior factors affecting workplace safety in ice and drinking water manufacturing factories in Samut Sakhon Province; and 2) examine working environment factors affecting workplace safety in ice and drinking water manufacturing factories in Samut Sakhon Province. A questionnaire was used as the research instrument to collect data from 100 Myanmar employees in Samut Sakhon Province. The statistics used for data analysis included descriptive statistics and simple linear regression analysis. The results revealed that: 1) work behavior factors explained approximately 37.5% of the variance in workplace safety; and 2) working environment factors explained approximately 35.9% of the variance in workplace safety. Appropriate work behavior and a good working environment significantly increased workplace safety among Myanmar employees at the 0.05 level of statistical significance.